2000
DOI: 10.1063/1.1305838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of AlxGa1−xN-based Schottky barrier photodiodes

Abstract: Schottky barrier photovoltaic detectors have been fabricated on n-AlxGa1−xN(0⩽x⩽0.35) and p-GaN epitaxial layers grown on sapphire. Their characteristics have been analyzed and modeled, in order to determine the physical mechanisms that limit their performance. The influence of material properties on device parameters is discussed. Our analysis considers front and back illumination and distinguishes between devices fabricated on ideal high-quality material and state-of-the-art heteroepitaxial AlxGa1−xN. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 44 publications
8
54
2
Order By: Relevance
“…It can be seen from the left inset of Fig. 14 that the inverse square root of intensity increases linearly for all temperatures. The temperature dependence of rate, R, can be used to determine the activation energy of the irradiation-induced processes according to equation (15). On the other hand, our earlier studies of the temperature-induced CL intensity decay (Sec.…”
Section: Optical Studies Of Bulk Znomentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen from the left inset of Fig. 14 that the inverse square root of intensity increases linearly for all temperatures. The temperature dependence of rate, R, can be used to determine the activation energy of the irradiation-induced processes according to equation (15). On the other hand, our earlier studies of the temperature-induced CL intensity decay (Sec.…”
Section: Optical Studies Of Bulk Znomentioning
confidence: 99%
“…The relationship between minority carrier diffusion length and responsivity of Schottky photodiodes has been examined in great detail in Ref. [15]. Schottky photodiodes are among the simplest photovoltaic devices, where the non-equilibrium minority carriers, generated in the bulk of the semiconductor due to light absorption, are collected by the built-in field of the Schottky barrier deposited on the surface of the semiconductor.…”
Section: Cathodoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][15][16][17][18][19] One interest of electrical studies is to confirm the presence of the Mg dopants and their electrical activity, and to deduce microscopic parameters such as ionization energies, capture cross sections, spatial concentration profiles, etc. Another interest is to contribute to the basic understanding of the conduction mechanism in these structures as the performances of the various electronic and optoelectronic devices depend on the efficiency of the current injection and of the carrier generation or carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, its intrinsic solar blindness ͑for x у0.38) and the ability of operation under harsh conditions ͑high-temperature and high power levels͒ due to its wide band gap makes Al x Ga 1Ϫx N-based photodetectors attractive for high-performance solar-blind detection applications. Several research groups have demonstrated successful solarblind operation with Al x Ga 1Ϫx N photodetectors using photoconductive, 3,4 p -i -n, [5][6][7][8][9][10][11][12][13][14] metal-semiconductormetal ͑MSM͒, 15,16 and Schottky [17][18][19][20] detector structures. Cutoff wavelengths ( c ) as short as ϳ225 nm, an ultraviolet/ visible rejection over 5 orders of magnitude along with responsivities as high as 0.12 A/W at 232 nm were reported using a Al 0.7 Ga 0.3 N p -i -n detector structure.…”
mentioning
confidence: 99%